Two-port approached thoracoscopic carina reconstruction using natural bronchial bifurcation. Issue 1 (December 2016) - Qiu, Tong; Zhao, Yandong; Song, Jianfang; Fu, Bo; Xuan, Yunpeng; Jiao, Wenjie
Abstract Background Carina resection and reconstruction is a challenging procedure for thoracic surgeons. We describe a novel technique of thoracoscopic carina reconstruction using the natural bifurcation, following pulmonary resection of the lung neoplasm. To our knowledge, it is the first report of this kind. Case presentation A 71-year-old male diagnosed of squamous cell lung cancer received two-port approached video-assisted thoracoscopic right bilobectomy with carina resection after 2 cycles of neoadjuvant therapy. After the removal of right lower lobe and middle lobe, the 7 station lymph nodes were resected with the invaded carina and bronchial walls in an en-bloc fashion. The neocarina was reconstructed by the natural bifurcation between the right upper bronchus and the bronchus intermedius. Intraoperative blood loss was about 220 mL, and operative time was about 225 min. The postoperative course was uneventful. The pathological TNM stage was pT3N2M0, IIIA. Adjuvant chemotherapy using gemcitabine and cisplatin was administered for 4 cycles. Follow-up 6 months after surgery confirmed no stenosis and no signs of local recurrence by bronchoscopy and CT scan. Conclusions We consider that the surgical procedure described here is a new alternative strategy for carina resection and reconstruction in the similar situation. The minimally invasive method is safe and effective for this challenging operation.